Karakteristik dan Makna Nazam Karangan Ulama Aceh di Kabupaten Bireuen - Al Furqan Al Furqan; Nurrahmah Nurrahmah; Zakiatul Sadri (Jurnal Dedikasi Pendidikan, 2020)
This research entitled “The Characteristic and Meaning of Nazam Compositions by Aceh Moslem Scholars in Bireuen Regency. The number of data in this research were eleven data which consisted of five details data from participant’s record and six data which were obtained from manuscript text or Nazam documentation of Moslem Scholars and respondent. Data gathering was done by using the techniques of observation, interview, record, note, and documentation. The data were analyzed through steps of transcribed the data, classified or sorted the data, identified the data characteristic, and described the meaning of data. The findings of this research revealed that the characteristics of Nazam which were composed by Aceh Moslem Scholars in Bireuen Regency arranged of (1) stanza, (2) rhyme, (3) religious themes, (4) syllables variation number, (5) used Arabic vocabularies, (6) began with praises to Allah and greetings to the Prophet. Furthermore, the meanings of Nazam Composition by Aceh Moslem Scholars in Bireuen Regency consisted of (1) denotative meaning, (2) connotative meaning, (3) lexical meaning, (4) stylistic meaning, (5) interpretation meaning